Endoplasmic reticulum aminopeptidase 1 polymorphism Ile276Met is associated with atopic dermatitis and affects the generation of an HLA‐C associated antigenic epitope in vitro. (4th March 2019) - Niepiekło‐Miniewska, W.; Mpakali, A.; Stratikos, E.; Matusiak, Ł.; Narbutt, J.; Lesiak, A.; Kuna, P.; Wilczyńska, K.; Nowak, I.; Wiśniewski, A.; Zwolińska, K.; Ponińska, J.; et al.
Abstract: Background: Atopic dermatitis (AD) is a common inflammatory skin disease of complex aetiology, with interactions between susceptibility genes and environmental factors. We have previously described a protective effect of the KIR2DS1 gene encoding the natural killer cell receptor, whose ligands are HLA‐C molecules. Here, we found an association of HLA‐C*05:01 allele with AD. KIR‐HLA‐C interactions are affected by peptides presented by HLA‐C. The generation of these peptides is strongly influenced by endoplasmic reticulum aminopeptidases 1 and 2 (ERAP1 and ERAP2). Expression and activity of ERAP molecules depend on the polymorphisms of their genes. Objective: Possible associations of several single nucleotide polymorphisms (SNPs) in the ERAP1 and ERAP2 genes with susceptibility to AD. Methods: Peripheral blood DNA isolation from 318 patients and 549 controls. PCR‐SSO or PCR‐SSP for HLA‐C typing; TaqMan Genotyping Assay for ERAP typing. Results: Only one SNP in the ERAP1 gene, rs26618T>C, causing the amino acid change Ile276Met, had an association with AD. To gain insight on the functional role of this SNP, we produced recombinant variants differing only at position 276 (Ile or Met) and tested their aminopeptidase activity against a N‐terminally extended precursor LIVDRPVTLV of the HLA‐C*05:01 epitope IVDRPVTLV. Both ERAP1 variants were able to efficiently generate the epitope, although the 276Ile allotype was able to do this about 50% faster. Furthermore, both variants were quite inefficient in further degradation of the mature epitope. Finally, we found that the effect of 276Met on susceptibility to AD was seen only in KIR2DS1‐negative individuals, not protected by this KIR. Conclusion: Associations of HLA‐C*05:01 allele and rs26618T>C (Ile276Met) ERAP1 polymorphism with AD, and a significant difference between these two ERAP1 variants in their ability to generate an epitope for the HLA‐C*05:01 molecule was found.